Frequency modulation systems in childrens and teens users of cochlear implant (Research, Society and Development, 2020)
Purpose: Verify the benefits of the use of the Frequency Modulated (FM) System for students who use cochlear implants, comparing different hearing conditions. Methods:  an analytical transversal study of a qualitative and quantitative character. Parents and teachers were invited to respond to the questionnaire “Frequency Modulated System Evaluation” allowing individual evaluation of the performance of individuals with the following hearing conditions: silence, solely auditory, with noise and at a distance. It is emphasized that the teachers responded to the questionnaire evaluating the performance of students with the use of the cochlear implant and the FM system while the parents only evaluated the use of the cochlear implants. A descriptive analysis was conducted of the variables and to verify the correlation between them, the non-parametric Mann-Whitney test was used and the Median test. Results: Nineteen users of cochlear implants and the FM system were contacted, but only seven individuals responded. Among the hearing conditions evaluated it was found that the items noise and distance had the best results with the use of the FM system, although there was no significant difference between the responses to the questionnaires with and without FM for any of the situations evaluated. Conclusion: The main benefits of the use of the FM system in conjunction with the cochlear implant were revealed in the conditions of hearing with competitive noise and at a distance.